MIR4435-2HG in exosomes promotes gastric carcinogenesis by inducing M2 polarization in macrophages - Li, Chaofeng; Chen, Zhengju; Gao, Jinli; Tang, Tao; Zhou, Lei; Zhang, Guochao; Zhang, Dongdong; Shen, Chao; Guo, Lei; Fu, Tao (Frontiers in Oncology, 2022)
Gastric cancer (GC) is a cancer with a high mortality rate. lncRNAs play a role in regulating GC tumorigenesis. In this paper, we analyzed differentially expressed lncRNAs between GC and adjacent normal tissues using multiple bioinformatics tools to identify new potential targets in GC. Cell viability and migration ability were detected using the Cell Counting Kit-8 (CCK-8) and transwell assays, MIR4435-2HG was negatively correlated with the survival rate of GC patients, and by inhibiting the activity of MIR4435-2HG, the viability and migration ability of GC cells could be reduced. In addition, RT- qPCR and western blot to detect gene and protein level expression, transmission electron microscopy and nanoparticle tracking analysis (NTA) to study the efficiency of exosome isolation, and flow cytometry to observe cell differentiation were employed, delivery of MIR4435-2HG shRNA via MKN45 cell-derived exosomes significantly reversed the MKN45 exosome-induced M2 polarization in macrophages. Furthermore, the low expression of MIR4435-2HG in MKN45 cell-derived exosomes inhibited the Jagged1/Notch and JAK1/STAT3 pathways in macrophages; MIR4435-2HG downregulated exosomes were found to significantly inhibit GC tumor growth in vivo by establishing a mouse model. In short, MKN45 cell-derived exosomes deliver lncRNA MIR4435-2HG, which promotes gastric carcinogenesis by inducing macrophage M2 polarization.